Electrostatically driven dielectric anomaly in mesoscopic ferroelectric–paraelectric bilayers. (15th February 2016) - Khassaf, H.; Khakpash, N.; Vijayan, S.; Aindow, M.; Alpay, S.P.
Abstract: We study the dielectric properties of 220 nm thick PbZr0.2 Ti0.8 O3 /SrTiO3 (PZT/STO) ferroelectric (FE)–paraelectric (PE) bilayers with varying PZT/STO layer fractions grown onto Pt/Ti/TiO2 /SiO2 /Si substrates using metal–organic solution deposition. The films are characterized using a combination of X–ray diffraction and scanning transmission electron microscopy (STEM). A λ–type anomaly in the dielectric response is observed near a critical PZT/STO ratio of 0.25 STO. At this layer fraction, the small–signal dielectric permittivity exceeds 1600, which is significantly larger that the dielectric response of monolithic PZT and STO films deposited at the same conditions (∼600 and ∼200, respectively). In order to explain this behavior, a thermodynamic model is employed taking into account the electrostatic and electromechanical interactions between PZT and STO layers. We conclude that the observed dielectric anomaly is due to internal fields that result from the polarization mismatch between FE PZT and PE STO layers. Our results indicate that such internal fields can be used as a design parameter to produce structures with enhanced dielectric, piezoelectric, and pyroelectric properties as compared to those achievable for monolithic monolayer ferroelectric materials. Graphical abstract: